2003
DOI: 10.1093/nar/gkg661
|View full text |Cite
|
Sign up to set email alerts
|

Apoptin protein multimers form distinct higher-order nucleoprotein complexes with DNA

Abstract: The chicken anaemia virus-derived protein apoptin is a tumour-specific cell-killing agent. It is biologically active as a highly stable, multimeric complex, consisting of 30-40 monomers. In tumour cells, but negligibly in normal cells, apoptin is imported into the nucleus prior to the induction of apoptosis. Immunoelectron microscopic data we report here indicate that apoptin predominantly co-localises with heterochromatin and nucleoli within tumour cells. Apoptin's preference for these DNA-dense nuclear bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Rohn et al (10) have recently reported that apoptin/VP3 contains a C-terminal, tumor-selective nuclear localization sequence (NLS) that requires activation by a tumor-selective phosphorylation at Thr108 (10). Several papers from 2003 have shown that assembly of a 30-to 40-VP3-unit apoptin/VP3 multimer in the cytoplasm is a prerequisite for nuclear import and induction of apoptosis (4,5,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rohn et al (10) have recently reported that apoptin/VP3 contains a C-terminal, tumor-selective nuclear localization sequence (NLS) that requires activation by a tumor-selective phosphorylation at Thr108 (10). Several papers from 2003 have shown that assembly of a 30-to 40-VP3-unit apoptin/VP3 multimer in the cytoplasm is a prerequisite for nuclear import and induction of apoptosis (4,5,11).…”
mentioning
confidence: 99%
“…Recent reports of an aggregate assembly step prior to nuclear import (4,5,11) raised our concern that the putative tumor-selective nuclear accumulation might be due to high levels of apoptin/VP3 expression and not to tumorigenic status. Therefore, we transfected transformed 3T3ras cells with a limiting dilution of the GFP-VP3 70-121 expression vector while maintaining a constant total DNA concentration by adding empty plasmid vector.…”
mentioning
confidence: 99%
“…Interestingly, Apoptin has been found to bind to DNA and colocalize with heterochromatin, which is predominantly transcriptionally inactive. 26 Similar to DEDD, Apoptin appears to be regulated by translocation to the nucleus, although nuclear localization of Apoptin is not sufficient to induce apoptosis and its phosphorylation appears to be required as well. 14 The finding that Apoptin binds to DEDAF is interesting, because it hints at a possible role of transcription repression in Apoptininduced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 Exhibiting basic properties (pK ~10.6), apoptin will interact directly with heterochromatin and with DNA ends, thus, it may interfere with gene transcription, DNA synthesis and DNA repair. 21 The choice of combining apoptin expression with mi-RNA-based surviving inhibition for cancer therapy is brilliant as both molecules have diverse, multiple, yet partly overlapping targets in the cell. It is…”
mentioning
confidence: 99%